Large-scale preparation of sialyl-Tn antigen-containing peptides from mucin-like glycoproteins in boar seminal gel. Issue 9 (23rd June 2021) - Takeuchi, Ryota; Maeda, Megumi; Nakano, Miran; Funahashi, Hiroaki; Kimura, Yoshinobu
ABSTRACT: Sialyl-Tn antigen, a tumor antigen, is a valuable ligand for the purification of proteins that specifically bind to it. Here, we developed a new method for the preparation of large amounts of sialyl-Tn antigen-containing peptides from an unused resource, boar seminal gel. The glycopeptides were prepared from the actinase E digests by a combination of gel filtration and hydrophilic partitioning.